2011
DOI: 10.1111/j.1365-2591.2011.01929.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hyperosmosis or high pH on a dual‐species biofilm of Enterococcus faecalis and Pseudomonas aeruginosa: an in vitro study

Abstract: Hyperosmosis effectively reduced a dual-species biofilm of E. faecalis and P. aeruginosa, whilst high pH had limited bactericidal effect in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 63 publications
1
38
0
Order By: Relevance
“…1,2 It has been shown that it is impossible to eradicate E. faecalis during treatment, and surviving cells can reside within dentinal tubules and remain viable in root-filled teeth for long periods. 3 The persistence of this species in treated root canals is attributed to its ability to resist the medicaments used during treatment, especially the antibacterial effect of calcium hydroxide, [4][5][6] which is one of the most effective and commonly used endodontic medicaments because of its bactericidal effects derived from its strong alkaline properties. 4 Several mechanisms by which E. faecalis survives extreme alkaline environments have been proposed.…”
mentioning
confidence: 99%
“…1,2 It has been shown that it is impossible to eradicate E. faecalis during treatment, and surviving cells can reside within dentinal tubules and remain viable in root-filled teeth for long periods. 3 The persistence of this species in treated root canals is attributed to its ability to resist the medicaments used during treatment, especially the antibacterial effect of calcium hydroxide, [4][5][6] which is one of the most effective and commonly used endodontic medicaments because of its bactericidal effects derived from its strong alkaline properties. 4 Several mechanisms by which E. faecalis survives extreme alkaline environments have been proposed.…”
mentioning
confidence: 99%
“…, van der Waal et al . ). Moreover, the extreme pH cannot be achieved within dentinal tubules because of the buffering effects of dentine (Haapasalo et al .…”
Section: Introductionmentioning
confidence: 97%
“…More largely our study highlights the potential use of NaCl as a basic but important component of the therapeutic arsenal used in the management of infectious diseases. Hyperosmotic stress is known for reducing biofilm growth and for being bactericidal on Escherichia coli , P. aeruginosa, and Enterococcus faecalis when NaCl is used at 13% to 35% and could be used for treatment of root canal infection [28] or for locking tunneled hemodialysis catheters [29]. Considering the lower NaCl concentrations used in this study, the antimicrobial effect was probably not related to a direct hyperosmotic lysis.…”
Section: Discussionmentioning
confidence: 79%